Nocturnal Continuous Positive Airway Pressure (nCPAP) Decreases High-Sensitivity C-Reactive Protein (hs-CRP) in Obstructive Sleep Apnea-Hypopnea Syndrome. (2nd November 2020) - Msaad, Sameh; Chaabouni, Akram; Marrakchi, Rim; Boudaya, Mariem; Kotti, Amina; Feki, Walid; Jamoussi, Kamel; Kammoun, Samy
Abstract : Background . Systemic and airway inflammation has recently been linked to obstructive sleep apnea-hypopnea syndrome (OSAHS) and is considered to be a probable risk factor for OSAHS-induced cardiovascular damage. High-sensitivity C-reactive protein (hs-CRP), as an inflammatory mediator, may be useful for the prediction of the risk of cardiovascular disease (CVD) and assessment of nocturnal continuous positive airway pressure (nCPAP) therapy effect in OSAHS patients. Methods . A prospective, controlled, cross-sectional study was conducted on 64 consecutive adult subjects with suspected sleep-disordered breathing (SDB). Results . OSAHS was confirmed in 43 patients (24 normotensive and 19 hypertensive patients) and ruled out in 21 normotensive subjects (controls). The median plasma level of hs-CRP did not differ significantly between OSAHS patients and controls. It showed an unmarked rise with the severity of OSAHS (p = 0.20 ) and was not correlated with AHI (p = 0.067 ; r = 0.28 ). After adjusting for cervical perimeter (CP), waist-to-hip ratio (WHR), and blood sugar level, hs-CRP level of 1 mg/dL or greater was significantly more often observed in OSAHS patients compared with controls (p = 0.032 ; OR = 5.60 ) and was also significantly associated with AHI (p = 0.021 ). A significant decrease in the median plasma hs-CRP level was observed in CPAP compliant patients (p = 0.006 ). Of those, only normotensive patients showed a significant decrease in plasma hs-CRP level. In hypertensive ones, however, the hs-CRP level dropped but not significantly. Using a linear regression model, the change in hs-CRP level ( Δ hs-CRP) following a 6-month-nCPAP therapy was found to positively correlate with the baseline hs-CRP level for both hypertensive (p = 0.02 ; r = 0.68 ), and even more normotensive OSAHS patients (p < 0.0001 ; r = 0.89 ). Conclusion . nCPAP therapy may have a cardiovascular protective effect in OSAHS patients. hs-CRP level would be useful as a valuable predictor of success in OSAHS treatment monitoring.